Miltefosine Against Scedosporium and Lomentospora Species: Antifungal Activity and Its Effects on Fungal Cells - Rollin-Pinheiro, Rodrigo; Almeida, Yuri de Castro; Rochetti, Victor Pereira; Xisto, Mariana Ingrid Dutra da Silva; Borba-Santos, Luana Pereira; Rozental, Sonia; Barreto-Bergter, Eliana (Frontiers in Cellular and Infection Microbiology, 2021)
Scedosporium and Lomentospora species are filamentous fungi responsible for a wide range of infections in humans and are frequently associated with cystic fibrosis and immunocompromising conditions. Because they are usually resistant to many antifungal drugs available in clinical settings, studies of alternative targets in fungal cells and therapeutic approaches are necessary. In the present work, we evaluated the in vitro antifungal activity of miltefosine against Scedosporium and Lomentospora species and how this phospholipid analogue affects the fungal cell. Miltefosine inhibited different Scedosporium and Lomentospora species at 2–4 µg/ml and reduced biofilm formation. The loss of membrane integrity in Scedosporium aurantiacum caused by miltefosine was demonstrated by leakage of intracellular components and lipid raft disorganisation. The exogenous addition of glucosylceramide decreased the inhibitory activity of miltefosine. Reactive oxygen species production and mitochondrial activity were also affected by miltefosine, as well as the susceptibility to fluconazole, caspofungin and myoricin. The data obtained in the present study contribute to clarify the dynamics of the interaction between miltefosine and Scedosporium and Lomentospora cells, highlighting its potential use as new antifungal drug in the future.